The physical map of wheat chromosome 5DS revealed gene duplications and small rearrangements - Akpinar, Bala Ani; Magni, Federica; Yuce, Meral; Lucas, Stuart J; Šimková, Hana; Šafář, Jan; Vautrin, Sonia; Bergès, Hélène; Cattonaro, Federica; Doležel, Jaroslav; Budak, Hikmet (BMC genomics, 2015)
BACKGROUND: The substantially large bread wheat genome, organized into highly similar three sub-genomes, renders genomic research challenging. The construction of BAC-based physical maps of individual chromosomes reduces the complexity of this allohexaploid genome, enables elucidation of gene space and evolutionary relationships, provides tools for map-based cloning, and serves as a framework for reference sequencing efforts. In this study, we constructed the first comprehensive physical map of wheat chromosome arm 5DS, thereby exploring its gene space organization and evolution. RESULTS: The physical map of 5DS was comprised of 164 contigs, of which 45 were organized into 21 supercontigs, covering 176 Mb with an N50 value of 2,173 kb. Fifty-eight of the contigs were larger than 1 Mb, with the largest contig spanning 6,649 kb. A total of 1,864 molecular markers were assigned to the map at a density of 10.5 markers/Mb, anchoring 100 of the 120 contigs (>5 clones) that constitute ~95 % of the cumulative length of the map. Ordering of 80 contigs along the deletion bins of chromosome arm 5DS revealed small-scale breaks in syntenic blocks. Analysis of the gene space of 5DS suggested an increasing gradient of genes organized in islands towards the telomere, with the highest gene density of 5.17 genes/Mb in the 0.67-0.78 deletion bin, 1.4 to 1.6 times that of all other bins. CONCLUSIONS: Here, we provide a chromosome-specific view into the organization and evolution of the D genome of bread wheat, in comparison to one of its ancestors, revealing recent genome rearrangements. The high-quality physical map constructed in this study paves the way for the assembly of a reference sequence, from which breeding efforts will greatly benefit.
Keywords: fyzikální mapování chromozomů; Physical Chromosome Mapping; Gene Rearrangement; kontigové mapování; Evolution, Molecular; Contig Mapping; Chromosomes, Plant; Triticum; genová přestavba; pšenice; DNA, Plant; chromozomy rostlin; Gene Duplication; duplikace genu; molekulární evoluce; DNA rostlinná